High Cellulose Purity by Acid Hydrolysis Pretreatment on Kenaf Outer Bast - Virginia Ghita Firsty; Ji Yeon Jeong; Yang Mo Gu; Jin Hyung Lee; Soo-Jeong Shin (Applied Sciences, 2022)
Acid hydrolysis treatment of kenaf outer bast fiber can produce pure cellulose content and hydrolyzed hemicellulose to monosaccharides. The effects of various reaction temperatures (110–130 °C), acid concentrations of sulfuric acid (0.25–1.00 N), and reaction times (60–120 min) were investigated as the optimum condition to gain pure cellulose content. A 1H NMR spectroscopy was used to analyze the carbohydrate content in the reaction of acid hydrolysis treatment. The results showed that optimum conditions for acid hydrolysis refer to two treatment prospects. First, a higher reaction temperature of 130 °C was necessary to increase the reaction for the hydrolyzes of hemicellulose—the high yield content produced by 0.25 N sulfuric acid with a short reaction time of 60 min. to improve the purity of cellulose, provided by the high sulfuric acid solution of 1.00 N for 120 min. Hemicellulose was hydrolyzed at almost 100% based on the two optimal conditions. The analysis revealed that a high temperature of acid hydrolysis was the primary treatment to hydrolyze hemicellulose to increase high pure cellulose from the kenaf outer bast fiber.